1994
DOI: 10.1901/jaba.1994.27-533
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Requests by Adults With Developmental Disabilities Using Incidental Teaching by Peers

Abstract: A peer‐delivered incidental‐teaching procedure was used to instruct appropriate requesting in adults with moderate to severe mental retardation or autism. Three pairs of group‐home residents participated in an incidental‐teaching procedure to increase appropriate requesting, prompting, and responding of residents during lunch‐preparation sessions. An increase in the number of incidental‐teaching episodes during dinner was obtained, and remained high when lunch‐making training sessions were withdrawn. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…This includes preschool children (e.g., Gena, Krantz, McClannahan, & Poulson, 1996;Goldstein, Kaczmarek, Pennington, & Shafer, 1992;Krantz & McClannahan, 1998;McGee, Almeida, Sulzer-Azaroff, & Feldman, 1992;Odom, Chandler, Ostrosky, McConnell, & Reaney, 1992;Sainato, Goldstein, & Strain, 1992) and youngsters in elementary school (e.g., L. K. Koegel, Koegel, Hurley, & Frea, 1992;Pierce & Schreibman, 1995;Stahmer & Schreibman, 1992;Taylor & Harris, 1995;Werts, Caldwell, & Wolery, 1996). There has been some research on teaching social skills to adolescents (e.g., Haring & Breen, 1992; R. L. Koegel & Frea, 1993) but relatively little with adults (e.g., Farmer-Dougan, 1994).…”
mentioning
confidence: 99%
“…This includes preschool children (e.g., Gena, Krantz, McClannahan, & Poulson, 1996;Goldstein, Kaczmarek, Pennington, & Shafer, 1992;Krantz & McClannahan, 1998;McGee, Almeida, Sulzer-Azaroff, & Feldman, 1992;Odom, Chandler, Ostrosky, McConnell, & Reaney, 1992;Sainato, Goldstein, & Strain, 1992) and youngsters in elementary school (e.g., L. K. Koegel, Koegel, Hurley, & Frea, 1992;Pierce & Schreibman, 1995;Stahmer & Schreibman, 1992;Taylor & Harris, 1995;Werts, Caldwell, & Wolery, 1996). There has been some research on teaching social skills to adolescents (e.g., Haring & Breen, 1992; R. L. Koegel & Frea, 1993) but relatively little with adults (e.g., Farmer-Dougan, 1994).…”
mentioning
confidence: 99%
“…Incidental teaching emphasizes receiving an elaborated response from the individual, after they have initiated interest in an item or a topic (Hart & Risley, 1982). Incidental teaching has been shown to be a successful teaching methodology for building initiation skills and a wide variety of language and conversation skills (e.g., Farmer-Dougan, 1994;McGee, Krantz, & McClannahan, 1985. Perhaps most important, incidental teaching procedures have been shown to have substantial generalization benefits, compared to discrete trial teaching (McGee et al, 1985).…”
Section: Naturalistic Teaching Methodsmentioning
confidence: 99%
“…IT and MIT have been shown to enhance the generalization and initiation of receptive and expressive language skills Farmer-Dougan, 1994;Hart & Risley, 1975;McGee et al, 1983;McGee et al, 1985;Miranda-Linne & Melin, 1992;Neef, Walters, & Egel, 1984;Rogers-Warren & Warren, 1980;Warren et al, 1984), as well as social interaction skills (McGee, Almeida, Sulzer-Azaroff, in children with ASD. In addition, some studies have reported that IT results in greater generalization of acquired expressive language skills than DTT (Delprato, 2001;McGee et al, 1985;Miranda-Linne & Melin, 1992).…”
Section: Evidence Basementioning
confidence: 99%